The Influence of Debate Method, Traditional Teaching Method and Learning Motivation Towards Speaking Ability of the First Semester Students of STIE Prabumulih 2017 - Herlina Herlina; Baginda Simaibang; Mulyadi Mulyadi (ELTE Journal (English Languange Teaching and Education), 2018)
AbstractThis research is concerned with the influence of debate method, traditional teaching method and students’ learning motivation towards their speaking ability of the first semester of STIE Prabumulih 2017. In this study 60 students of the first semester of STIE Prabmulih 2017 in the academic year of 2017/2018 were chosen as the samples by means of cluster random sampling. This study applied factorial research design. The data were collected by using questionnaire and t-test. The data were analyzed by using Paired Sample t-test, Independent Sample t-test and Two Way Anova. Theresults showed that, first there was a significant difference in speaking ability between the students with high learning motivation and those with low learning motivation taught using debate method. Second there was a significant difference in speaking ability between the students with high learning motivation and those with low learningmotivation taught using traditional teaching method. Third there was a significant difference in speaking ability between the students with high learning motivation and those with low learning motivation taught using debate method and traditional teaching method. Last, there were not any significant interaction effects of debate method andlearning motivation towards the students’ speaking ability. The Finding suggests that there were significant influences of debate method, traditional method and students’ learning motivation towards their speaking ability of the first semester of STIE Prabumulih 2017.Keywords: Debate Method, Traditional Teaching Method, Learning Motivation, Speaking Ability